Educating chiropractic students about intraobserver and interobserver variability through the use of skinfold measurement. - McRae MP (Journal of Chiropractic Education (Association of Chiropractic Colleges))
Purpose: Skinfold measurements taken by novice observers are fraught with high rates of intraobserver variability and even higher rates of interobserver variability, and therefore having students collect and analyze skinfold measurements is an ideal way to present the concepts of both measurement and physiological variability. Methods: Students in a 1st trimester clinical biochemistry laboratory were assembled into groups of four, and within each group the students were asked to volunteer to be either a subject, a data recorder, or one of two observers. To demonstrate intraobserver versus interobserver variability the subject was assessed by four separate observers who each took four separate skinfold measurements. The skinfold measurement obtained from each separate observation was based on the sum of four skinfold sites. The average sums of the skinfold measurement (in mm) and standard deviations were calculated and posted for postlaboratory discussion. Results: Skinfold measurements were taken on 76 1st-trimester chiropractic students (46 males and 30 females). The average intraobserver and interobserver variability across all 76 participants was 4.8 ± 2.3mm and 10.0 ± 6.3mm, respectively, representing a twofold increase in variability, which was statistically significant ( p< .0001). The noticeable differences between intraobserver and interobserver variability provided a great back drop for postlab discussion, which was the intended purpose of performing this demonstration project. Conclusion: Measuring skinfold thickness can prove to be a useful and inexpensive method for easily and safely demonstrating the concepts of variability to students.